Negative electrode material and preparation method thereof, battery and terminal

By covering the metal oxide and/or the coating layer formed by composite of silicon-based or tin-based material on the core surface of the silicon-based or tin-based material, the problems of volume expansion and high surface activity of the silicon-based negative electrode material are solved, and better cycling performance and conductivity are achieved.

CN115763803BActive Publication Date: 2025-05-02HUAWEI TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202211341721.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2019-11-30
Publication Date
2025-05-02
Estimated Expiration
2039-11-30

AI Technical Summary

Technical Problem

The volume expansion and contraction of the silicon-based negative electrode material during the deintercalation reaction leads to the damage of the electrode structure, and the high surfactivity leads to the exhaustion of the electrolyte and the battery capacity rapidly attenuates.

Method used

A cladding layer formed by composite of metal oxides and/or silicon oxides with carbon is coated on the core surface of the silicon-based or tin-based material to form a conductive carbon network to alleviate volume expansion and reduce surface activity.

Benefits of technology

It effectively alleviates the volume expansion of silicon-based or tin-based materials, reduces surface activity, improves the cycling performance and overall conductivity of the negative electrode materials, and extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115763803B_ABST
    Figure CN115763803B_ABST
Patent Text Reader

Abstract

An embodiment of the present invention provides a negative electrode material, including a core and a coating layer coated on the surface of the core, wherein the core is a silicon-based material or a tin-based material, and the coating layer includes a first carbon material and oxides / carbon microspheres dispersed in the first carbon material, wherein the oxides / carbon microspheres are secondary particles formed by a composite of nano-oxide particles and a second carbon material, wherein the nano-oxide particles include one or more of metal oxide particles and silicon oxide particles, and the first carbon material and the second carbon material are continuously distributed to form a conductive carbon network. Among them, the coating layer can effectively alleviate the volume expansion of the core, reduce the surface activity of the core, and has high strength and high electronic and ionic conductivity. An embodiment of the present invention also provides a method for preparing the negative electrode material, as well as a battery and a terminal containing the negative electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application. The application number of the original application is CN201911217109.X, and the original application date is November 30, 2019. The entire contents of the original application are incorporated into this application by reference. Technical Field

[0002] The embodiments of the present invention relate to the technical field of lithium-ion batteries, and in particular to negative electrode materials and preparation methods thereof, batteries and terminals. Background Art

[0003] Silicon has a theoretical specific capacity of 4200mAh / g and is one of the most studied negative electrode materials that can replace graphite. However, silicon will undergo a dramatic volume expansion (0-300%) and contraction during the lithium extraction reaction, which will lead to the destruction of the electrode structure, and the silicon surface will continuously produce a new SEI film (solid electrolyte interface) with the electrolyte, which will lead to the exhaustion of the electrolyte and the rapid decay of the battery capacity. In addition, most electrolytes currently use carbonates as solvents, which are easy to decompose on the electrode surface to produce gas, causing battery bloating.

[0004] In order to alleviate the volume expansion of silicon, reduce the surface activity of silicon, and improve the cycle performance, the industry's commonly used method is to carbon-coat the surface of the silicon negative electrode. However, the carbon coating structure is relatively fragile and can be easily damaged after long-term repeated charging, causing rapid capacity decay. Summary of the invention

[0005] In view of this, an embodiment of the present invention provides a negative electrode material, the surface of which has a coating layer formed by a metal oxide and / or silicon oxide and a carbon composite. The coating layer can effectively alleviate the volume expansion of the negative electrode material, reduce the surface activity of the negative electrode material, and has high strength, so as to solve to a certain extent the problem of poor battery cycle performance caused by the low strength of the carbon coating structure on the surface of the existing silicon-based negative electrode material.

[0006] Specifically, a first aspect of an embodiment of the present invention provides a negative electrode material, comprising a core and a coating layer coated on the surface of the core, wherein the core is a silicon-based material or a tin-based material, and the coating layer comprises a first carbon material and oxide / carbon microspheres dispersed in the first carbon material, wherein the oxide / carbon microspheres are secondary particles composited of nano-oxide particles and a second carbon material, wherein the nano-oxide particles comprise one or more of metal oxide particles and silicon oxide particles, and the first carbon material and the second carbon material are continuously distributed to form a conductive carbon network.

[0007] In an embodiment of the present invention, the particle size of the nano-oxide particles is less than or equal to 10 nm.

[0008] In an embodiment of the present invention, the particle size of the oxide / carbon microspheres is 50 nm-1 μm.

[0009] In an embodiment of the present invention, the nano oxide particles and the second carbon material are uniformly distributed inside the oxide / carbon microspheres.

[0010] In an embodiment of the present invention, part or all of the first carbon material and the second carbon material are homogeneous carbon. Homogeneous means that the material is composed of the same units and the characteristics of each part are the same.

[0011] In an embodiment of the present invention, the metal oxide particles include one or more metal oxide particles formed by one or more metal elements of Mg, Al, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn and Li and oxygen.

[0012] In an embodiment of the present invention, the mass of the coating layer accounts for 1%-20% of the total mass of the negative electrode material.

[0013] In an embodiment of the present invention, in the coating layer, the mass content of the nano oxide particles is 20%-90%.

[0014] In an embodiment of the present invention, the coating layer has a thickness of 100 nm-5 μm.

[0015] In an embodiment of the present invention, the silicon oxide particles have a silicon-oxygen atomic ratio of 1:1.2-2.

[0016] In the embodiment of the present invention, the specific surface area of ​​the negative electrode material is 1-20m 2 / g.

[0017] In an embodiment of the present invention, the silicon-based material includes one or more of elemental silicon, silicon oxide, silicon carbon, and silicon alloy.

[0018] In an embodiment of the present invention, the tin-based material includes one or more of elemental tin and tin oxide.

[0019] In an embodiment of the present invention, the particle size of the core is 500nm-50μm.

[0020] In an embodiment of the present invention, the negative electrode material further includes a protective layer disposed on the surface of the coating layer, and the material of the protective layer includes a carbon material and / or a conductive polymer.

[0021] The negative electrode material provided in the first aspect of the embodiment of the present invention effectively alleviates the volume expansion of the silicon-based or tin-based material core and reduces the surface activity of the core material by coating the surface of the silicon-based or tin-based material core with a coating layer composed of oxide / carbon microspheres and carbon material, thereby reducing the decomposition and gas production of the electrolyte on the electrolytic surface and improving the long-cycle performance of the material. Moreover, since the oxide / carbon microspheres are secondary particles composed of nano-oxide particles and carbon materials, the strength of the coating layer is guaranteed, and the good conductive connection between the nano-oxide particles is also guaranteed, thereby improving the cycle performance and overall conductivity of the negative electrode material.

[0022] In a second aspect, an embodiment of the present invention further provides a method for preparing a negative electrode material, comprising:

[0023] Mixing an oxide precursor, a carbon source precursor, and a core material together, so that the oxide precursor and the carbon source precursor form an oxide / carbon microsphere precursor in situ on the surface of the core material, to obtain a core material with the oxide / carbon microsphere precursor coated on the surface; or

[0024] Firstly, the oxide precursor and the carbon source precursor are mixed to prepare an oxide / carbon microsphere precursor, and then the oxide / carbon microsphere precursor is coated on the core material to obtain a core material with the oxide / carbon microsphere precursor coated on the surface;

[0025] The core material whose surface is coated with an oxide / carbon microsphere precursor is subjected to a high-temperature carbonization treatment at 800°C-1100°C to obtain a negative electrode material, wherein the negative electrode material comprises a core and a coating layer coated on the surface of the core, wherein the core is a silicon-based material or a tin-based material, wherein the coating layer comprises a first carbon material and oxide / carbon microspheres dispersed in the first carbon material, wherein the oxide / carbon microspheres are secondary particles composited with nano-oxide particles and a second carbon material, wherein the nano-oxide particles comprise one or more of metal oxide particles and silicon oxide particles, and wherein the first carbon material and the second carbon material are continuously distributed to form a conductive carbon network.

[0026] In an embodiment of the present invention, during the high temperature carbonization process, the temperature is increased to 800°C-1100°C at a heating rate of 2-10°C / min.

[0027] In an embodiment of the present invention, the high temperature carbonization process is carried out under vacuum or protective atmosphere.

[0028] In an embodiment of the present invention, the core material with the surface coated with oxide / carbon microsphere precursor is prepared by one or more methods selected from the group consisting of sol-gel method, hydrothermal method and co-precipitation method.

[0029] In an embodiment of the present invention, the oxide precursor includes one or more of silane containing Si—O bonds, metal oxygen acid salts, metal alcohol compounds, and metal ester compounds.

[0030] In an embodiment of the present invention, the carbon source precursor includes one or more of phenols, aldehydes, thiophene, pyridine, pyrrole, aniline, and imidazole.

[0031] The preparation method provided in the second aspect of the embodiment of the present invention has a simple process, is easy to control, and is suitable for industrial production.

[0032] A third aspect of an embodiment of the present invention provides a battery, comprising a positive electrode plate, a negative electrode plate, a separator, and an electrolyte, wherein the negative electrode plate comprises a negative electrode active material, and the negative electrode active material comprises the negative electrode material described in the first aspect of the present invention.

[0033] The battery provided by the embodiment of the present invention has high capacity and better cycle performance and safety performance.

[0034] An embodiment of the present invention also provides a terminal, including a terminal shell, and a circuit board and a battery located inside the terminal shell, wherein the battery is electrically connected to the circuit board for powering the circuit board, and the battery includes the battery described in the third aspect of the embodiment of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 A schematic diagram of the structure of a lithium-ion battery provided by an embodiment of the present invention;

[0036] Figure 2 A schematic diagram of the structure of the negative electrode material provided in an embodiment of the present invention;

[0037] Figure 3 A schematic diagram of a partial structure of a coating layer of a negative electrode material provided in an embodiment of the present invention;

[0038] Figure 4 A schematic diagram of the structure of a terminal provided by an embodiment of the present invention;

[0039] Figure 5 This is a SEM (Scanning Electron Microscope) image of the Al2O3 / C@SiO negative electrode material prepared in Example 2 of the present invention;

[0040] Figure 6 This is a SEM (Scanning Electron Microscope) image of the SiOx / C microsphere precursor prepared in Example 3 of the present invention;

[0041] Figure 7The cycle curves of the batteries prepared using the negative electrode materials of Examples 1-3 of the present invention. DETAILED DESCRIPTION

[0042] The embodiments of the present invention will be described below in conjunction with the accompanying drawings in the embodiments of the present invention.

[0043] like Figure 1 As shown, the core components of a lithium-ion battery include a positive electrode material 101, a negative electrode material 102, an electrolyte 103, a diaphragm 104, and corresponding connecting accessories and circuits. Among them, the positive electrode material 101 and the negative electrode material 102 can deintercalate lithium ions to achieve energy storage and release, the electrolyte is a carrier for the transmission of lithium ions between the positive and negative electrodes, and the diaphragm 104 can pass lithium ions but is not conductive, thereby separating the positive and negative electrodes to prevent short circuits. Among them, the positive and negative electrode materials are the main parts that play the energy storage function, and are the most direct embodiment of the energy density, cycle performance and safety performance of the battery cell. Silicon-based negative electrode materials have attracted attention in the industry due to their high gram capacity. However, silicon-based negative electrode materials have large volume expansion and high surface activity, resulting in poor battery cycle performance. To solve this problem, an embodiment of the present invention provides a negative electrode material that has high capacity, high structural stability and high conductivity.

[0044] like Figure 2 and Figure 3 As shown, the negative electrode material 10 provided in an embodiment of the present invention has a core-shell structure, including a core 1 and a coating layer 2 coated on the surface of the core 1, wherein the core 1 can be a silicon-based material or a tin-based material, the coating layer 2 includes a first carbon material 21 and oxide / carbon microspheres 22 dispersed in the first carbon material 21, the oxide / carbon microspheres 22 are secondary particles composited by nano-oxide particles 221 and second carbon materials 222, the nano-oxide particles 221 include one or more of metal oxide particles and silicon oxide particles, and the first carbon material 21 and the second carbon material 222 are continuously distributed to form a conductive carbon network.

[0045] The negative electrode material provided by the embodiments of the present invention has a surface coating layer that can relieve the volume expansion of the core, reduce the surface activity of the core, and at the same time has high strength and high electron and ion conductivity, so as to have good charge-discharge cycle stability and fast charge-discharge ability. Among them, the oxide / carbon microspheres are composed of nano-oxide particles and carbon materials. The nano-oxide particles in the oxide / carbon microspheres have a certain rigidity as the "skeleton" structure and are structurally stable, which can limit the volume expansion of the core material; the second carbon material inside the oxide / carbon microspheres ensures good electrical connection between the nano-oxide particles, and the first carbon material between the oxide / carbon microspheres and the second carbon material inside the oxide / carbon microspheres continuously form a complete conductive carbon network, thus ensuring electron conduction both inside and between the microspheres at the same time. Moreover, the nano-oxide particles have a small size and a short ion diffusion path, so the overall conductivity of the negative electrode material is improved. In addition, the coating layer can prevent the core from directly contacting the electrolyte, reduce the surface activity of the core material, and reduce the side reactions occurring on the surface of the core by the electrolyte.

[0046] In the embodiments of the present invention, the core 1 is a high-capacity silicon-based material or a tin-based material. Among them, the silicon-based material can specifically be, but is not limited to, one or more of elemental silicon, silicon oxide, silicon carbide, and silicon alloy. The crystal form of the silicon-based material can be one or more of amorphous state and low crystalline state. When the core is silicon oxide, in its chemical general formula SiOₓ, x satisfies 0 < x ≤ 1.3. Silicon oxides with a higher silicon-oxygen atom ratio have higher capacity, which is beneficial to finally obtaining a high-capacity negative electrode material.

[0047] In the embodiments of the present invention, the tin-based material includes one or more of elemental tin and tin oxide.

[0048] In the embodiments of the present invention, the core 1 can be primary particles or secondary particles. In one embodiment of the present invention, the particle size of the core can be 500 nm - 50 μm. In another embodiment of the present invention, the particle size of the core can also be 1 μm - 30 μm. In other embodiments of the present invention, the particle size of the core can also be 10 μm - 20 μm.

[0049] In an embodiment of the present invention, the nano-oxide particles 221 may specifically be oxide particles having a particle size less than or equal to 10 nm. The nano-oxide particles 221 are primary oxide particles. The reason for selecting nano-oxide particles with a smaller particle size is that in nano-oxide particles with a smaller particle size, the diffusion path of active ions is shorter, which is beneficial to the transmission of active ions (lithium ions) and effectively improves the ionic conductivity of the material. In one embodiment of the present invention, the particle size of the nano-oxide particles 221 may be less than or equal to 5 nm. Specifically, the particle size of the nano-oxide particles 221 may be 0.5 nm-5 nm. The particle size of the nano-oxide particles 221 may be, for example, 0.5 nm, 1 nm, 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, 10 nm.

[0050] In an embodiment of the present invention, the nano oxide particles 221 may specifically be metal oxide particles or silicon oxide particles. In one embodiment of the present invention, the oxide / carbon microspheres 22 may be composed of metal oxide particles and carbon materials; in another embodiment of the present invention, the oxide / carbon microspheres 22 may also be composed of silicon oxide particles and carbon materials; in another embodiment of the present invention, the oxide / carbon microspheres 22 may also be composed of metal oxide particles, silicon oxide particles and carbon materials. In an embodiment of the present invention, the oxide / carbon microspheres 22 may contain one or more metal oxide particles. In an embodiment of the present invention, in each metal oxide particle, the metal element may be one or more of Mg, Al, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn and Li. That is, the metal oxide may be a monovalent, divalent or polyvalent metal oxide, that is, the metal oxide may contain one, two or more metal elements at the same time. When the metal oxide is a monometallic oxide, the metal oxide particles may specifically be, but are not limited to, one or more of magnesium oxide particles, titanium oxide particles, aluminum oxide particles, vanadium oxide particles, chromium oxide particles, iron oxide particles, manganese oxide particles, cobalt oxide particles, zirconium oxide particles, copper oxide particles, lithium oxide particles, nickel oxide particles, and zinc oxide particles. The volume expansion of these oxides after lithium insertion is smaller than that of the core, and the structure is relatively stable. Using them as coating materials is beneficial to improving the strength of the coating and improving the structural stability of the negative electrode material. Among them, the selection of titanium oxide particles and silicon oxide particles can provide a higher lithium insertion capacity than carbon, thereby improving the overall capacity of the negative electrode material. In an embodiment of the present invention, when silicon oxide particles are selected, the silicon-oxygen atomic ratio in the silicon oxide particles may be 1:1.2-2, and further may be 1:1.5-2. Selecting a silicon oxide compound with a low silicon-oxygen ratio as a coating material can ensure low expansion and improve the structural stability of the negative electrode material.

[0051] In the embodiment of the present invention, the particle size of the oxide / carbon microspheres 22 is 50nm-1μm. Specifically, the particle size of the oxide / carbon microspheres can be, for example, 50nm, 100nm, 200nm, 300nm, 400nm, 500nm, 600nm, 700nm, 800nm, 900nm, 1μm. The particle size of the microspheres is small, and a small amount of microspheres can be used to coat the core, which is conducive to preparing a coating layer with a small thickness and uniform dispersion of microspheres to achieve a coating effect, while making the coating layer account for a relatively small mass of the overall negative electrode material, minimizing the impact on the material capacity performance.

[0052] In the embodiment of the present invention, nano oxide particles 221 and second carbon material 222 are evenly distributed inside oxide / carbon microspheres 22. Nano oxide particles 221 and second carbon material 222 are evenly distributed in oxide / carbon microspheres 22, and more specifically, metal elements and / or silicon elements, oxygen elements, and carbon elements are evenly distributed in the microspheres to form homogeneous composite microspheres. The even distribution of carbon in the microspheres can ensure good conductive connection between nano oxide particles.

[0053] In an embodiment of the present invention, the first carbon material 21 and the second carbon material 222 are not simply physically mixed, wherein part or all of the first carbon material 21 and the second carbon material 222 are homogeneous carbon structures formed at one time. Homogeneity means that the material is composed of the same units and the characteristics of each part are the same. The first carbon material 21 and the second carbon material 222 can be amorphous carbon, graphitized carbon, or a mixture of the two. In a specific embodiment of the present invention, the first carbon material 21 is formed by carbonization of the carbon source inside the oxide / carbon microsphere precursor, which overflows from the inside to the surface during high-temperature treatment. The second carbon material present inside the oxide / carbon microsphere ensures a good conductive connection between the nano-oxide particles, and the first carbon material present between the microspheres builds a bridge for electron transmission between the microspheres. The first carbon material and the second carbon material form a complete and continuous conductive network in the coating layer, thereby ensuring electron conduction inside and between the microspheres at the same time, and improving the overall electronic conductivity of the coating layer.

[0054] In the embodiment of the present invention, the mass of the coating layer can account for 1%-20% of the total mass of the negative electrode material. In the embodiment of the present invention, the mass proportion of the coating layer can also be 2%-8%. The core capacity is high and the coating layer capacity is low. Controlling the mass proportion of the coating layer can ensure the capacity of the negative electrode material.

[0055] In an embodiment of the present invention, the thickness of the coating layer may be 100 nm-5 μm. In one specific embodiment of the present invention, the thickness of the coating layer may be 500 nm-4 μm. In another specific embodiment of the present invention, the thickness of the coating layer may be 2 μm-3 μm.

[0056] In an embodiment of the present invention, the mass content of the oxide in the coating layer may be 20%-90%. In an embodiment of the present invention, the mass content of the oxide in the coating layer may also be 30%-70%. Although nano oxide particles have a certain rigidity, they have poor electrical conductivity, and although carbon materials have good electrical conductivity, they have low strength. By controlling the oxide in the coating layer to a suitable content, the carbon content of the coating layer can be ensured while improving the stability of the material structure, thereby improving the electrical conductivity of the material. In an embodiment of the present invention, the coating layer may be composed only of oxides and carbon materials, or may contain other conductive components besides carbon.

[0057] It should be noted that Figure 2 The structure of the middle coating layer is for illustration only and does not limit the coating layer to be composed of a single layer of uniformly arranged oxide / carbon microspheres.

[0058] In the embodiment of the present invention, the specific surface area of ​​the negative electrode material is 1-20m 2 / g. The negative electrode material has a small specific surface area and a small contact area with the electrolyte, which can reduce side reactions and is beneficial to improving the long cycle performance of the battery.

[0059] In an embodiment of the present invention, the surface of the negative electrode material further includes a protective layer disposed on the surface of the coating layer, and the material of the protective layer includes a carbon material and / or a conductive polymer. The conductive polymer may specifically be, but is not limited to, one or more of polyacetylene, polypyrrole, polythiophene, poly(3,4-ethylenedioxythiophene): poly(styrenesulfonic acid), polyaniline, polyphenylene, and polyphenyleneethylene. The thickness of the protective layer may be 5nm-50nm, and may further be 10nm-20nm. The provision of the protective layer may further enhance the conductivity of the negative electrode material.

[0060] The negative electrode material provided in the above-mentioned embodiment of the present invention effectively alleviates the volume expansion of the silicon-based or tin-based material core and reduces the surface activity of the core material by coating the surface of the silicon-based or tin-based material core with a coating layer composed of oxide / carbon microspheres and carbon material, thereby reducing the decomposition and gas production of the electrolyte on the electrolytic surface and improving the long-cycle performance of the material. Moreover, since the oxide / carbon microspheres are secondary particles composed of nano-oxide particles and carbon materials, the strength of the coating layer is guaranteed, and the good conductive connection between the nano-oxide particles is also guaranteed, thereby improving the cycle performance and overall conductivity of the negative electrode material.

[0061] Accordingly, an embodiment of the present invention further provides a method for preparing a negative electrode material, comprising:

[0062] Step (1): mixing an oxide precursor, a carbon source precursor, and a core material together, so that the oxide precursor and the carbon source precursor form an oxide / carbon microsphere precursor in situ on the surface of the core material, thereby obtaining a core material having a surface coated with the oxide / carbon microsphere precursor; or

[0063] Firstly, an oxide precursor and a carbon source precursor are mixed to prepare an oxide / carbon microsphere precursor, and then the oxide / carbon microsphere precursor is coated on the core material to obtain a core material with the oxide / carbon microsphere precursor coated on the surface;

[0064] Step (2): subjecting the obtained core material with the surface coated with oxide / carbon microsphere precursor to a high temperature carbonization treatment at 900°C-1100°C to obtain the above-mentioned negative electrode material.

[0065] In the embodiment of the present invention, in step (1), one or more methods selected from the group consisting of a sol-gel method, a hydrothermal method, and a co-precipitation method may be used to prepare a core material having a surface coated with an oxide / carbon microsphere precursor.

[0066] Among them, the sol-gel method uses a compound containing a highly chemically active component as a precursor, uniformly mixes these raw materials in a liquid phase, and performs hydrolysis and condensation chemical reactions to form a stable transparent sol system in the solution. After aging, the sol particles slowly polymerize to form a gel with a three-dimensional network structure. The gel network is filled with a solvent that has lost fluidity to form a gel. The gel is dried, sintered and solidified to prepare a nano-microstructured material. Specifically, the operation of preparing a core material with an oxide / carbon microsphere precursor coated on the surface by the sol-gel method can be: putting an oxide precursor, a carbon source precursor, and a core material together into the liquid phase of the sol-gel method synthesized microspheres, so that the oxide precursor and the carbon source precursor undergo hydrolysis and condensation reactions on the surface of the core material, and forming a core material coated with an oxide / carbon microsphere precursor in situ. In this process, the pH of the system can be adjusted by adding ammonia or other pH regulators to regulate the environment of the condensation reaction.

[0067] In one embodiment of the present invention, an oxide precursor, a carbon source precursor, and a core material are mixed together to prepare a core material having an oxide / carbon microsphere precursor coated on the surface in one step. In this embodiment, in the negative electrode material finally prepared, all the first carbon materials between the oxide / carbon microspheres and the second carbon materials in the microspheres are homogeneous carbon.

[0068] In another embodiment of the present invention, an oxide / carbon microsphere precursor is first prepared, and then the oxide / carbon microsphere precursor is coated with a core material, and a core material with a surface coated with an oxide / carbon microsphere precursor is prepared in two steps. Among them, the specific operation of coating the core material with an oxide / carbon microsphere precursor can be: after mixing the oxide / carbon microsphere precursor and the core material in a certain proportion, the two materials are evenly mixed at a certain speed by a ball mill or a fusion machine, and the oxide / carbon microsphere precursor is coated on the surface of the core material. In this embodiment, when the oxide / carbon microsphere precursor is used to coat the core material, another carbon source precursor is not introduced, then in the negative electrode material finally prepared, all the first carbon materials between the oxide / carbon microspheres and the second carbon materials in the microspheres are homogeneous carbon. If another carbon source precursor is introduced, then part of the first carbon material between the oxide / carbon microspheres and the second carbon material in the microspheres are homogeneous carbon, and another part of the first carbon material between the oxide / carbon microspheres and the second carbon material in the microspheres are non-homogeneous carbon.

[0069] In the embodiment of the present invention, the oxide precursor is the precursor material from which nano oxide particles can be finally obtained, and can be one or more of silane containing Si-O bonds, metal oxyacid salts, metal alcohol compounds, and metal ester compounds. When the oxide precursor is a metal organic containing a carbon chain or an organic silane containing Si-O bonds, the oxide precursor can also serve as a carbon source precursor, so there is no need to add an additional carbon source precursor. The silane containing Si-O bonds can specifically be an alkoxy-containing silane, such as triethoxyvinylsilane, trimethoxyvinylsilane, etc.

[0070] In an embodiment of the present invention, the carbon source precursor may be one or more of phenols, aldehydes, thiophene, pyridine, pyrrole, aniline, and imidazole. In a specific embodiment of the present invention, phenols and aldehydes are used to form a carbon network after condensation of phenolic aldehydes.

[0071] In the embodiment of the present invention, in order to obtain the oxide / carbon microsphere structure, it is ensured that the metal element or silicon element is evenly distributed with the carbon element in the precursor, and the metal oxide precursor and the carbon source precursor whose oxide nucleation speed is comparable to the carbon network formation speed can be selected. Wherein, the formation mode of the carbon network can be condensation, polymerization or polycondensation reaction. For example, when the oxide / carbon microsphere precursor is prepared by the sol-gel method, the oxide precursor and the carbon source precursor whose oxide nucleation speed is similar to the carbon network formation speed in the liquid phase can be selected, and the oxide precursor and the carbon source precursor can be mixed together in the liquid phase, and the oxide nucleation and carbon network formation occur synchronously to obtain the target oxide / carbon microsphere precursor. Of course, the synthesis of oxide / carbon microsphere precursors with different carbon contents can be achieved by adjusting the ratio of the oxide precursor and the carbon source precursor. In addition, if the oxide precursor is a metal organic containing a carbon chain or a silane containing a Si-O bond, the step of adding an additional carbon source precursor can also be omitted, that is, the oxide precursor and the carbon source precursor are the same substance, such as a metal alkoxide.

[0072] In the embodiment of the present invention, in step (1), the oxide / carbon microsphere precursor can be collected by centrifugation, washing, drying and the like.

[0073] In the embodiment of the present invention, in step (2), the oxide / carbon microsphere precursor coating layer can be further sintered and solidified by high temperature treatment, carbonization and dehydration reactions occur, and oxide / carbon microspheres with uniform distribution of metal elements and / or silicon elements and carbon elements are obtained. At the same time, during the high temperature curing process, by controlling the temperature curve, the carbon source part inside the oxide / carbon microsphere can be diffused to the outside of the microsphere, and after carbonization, carbon connections will be formed between the microspheres, that is, the first carbon material. The temperature of the high temperature carbonization treatment can be selected according to the specific material, for example, it can be 800°C, 900°C, 1000°C, 1100°C. In the embodiment of the present invention, the temperature can be increased to 800°C-1100°C at a heating rate of 2-10°C / min. The time of the high temperature carbonization treatment can be 3-8 hours. The high temperature carbonization treatment can be carried out in a vacuum or protective atmosphere, and the protective atmosphere can be an inert atmosphere, a reducing atmosphere, or a mixed atmosphere of an inert atmosphere and a reducing atmosphere. The inert atmosphere can be nitrogen, argon, helium, etc., and the reducing atmosphere can be hydrogen.

[0074] The preparation method provided by the embodiment of the present invention has simple process, is easy to control, and is suitable for industrial production.

[0075] The embodiment of the present invention further provides a battery, comprising a positive electrode plate, a negative electrode plate, a separator, and an electrolyte, wherein the negative electrode plate comprises the negative electrode material provided in the embodiment of the present invention. Specifically, the battery can be a lithium-ion battery. The battery provided in the embodiment of the present invention has a high capacity and has better cycle performance and safety performance. The battery provided in the embodiment of the present invention can be used in terminal consumer products, such as mobile phones, tablet computers, portable computers, laptop computers, and other wearable or portable electronic devices.

[0076] like Figure 4 As shown, an embodiment of the present invention further provides a terminal 200, which can be a mobile phone, or an electronic product such as a tablet computer, a laptop computer, a portable machine, a smart wearable product, etc. The terminal 200 includes a shell 201 assembled on the outside of the terminal, and a circuit board and a battery (not shown in the figure) located inside the shell 201. The battery is electrically connected to the circuit board to power the circuit board, wherein the battery is the battery provided in the above-mentioned embodiment of the present invention, and the shell 201 may include a front shell assembled on the front side of the terminal and a back cover assembled on the back side, and the battery can be fixed on the inside of the back cover.

[0077] The embodiments of the present invention are further described below with reference to a plurality of embodiments.

[0078] Example 1

[0079] A SiO 1.5 A method for preparing a Si negative electrode material coated with a C / C microsphere, comprising:

[0080] (1) Mix 20 mL of ethanol and 10 mL of deionized water, weigh 0.3 g of resorcinol and put it into the ethanol / water mixed solution, stir for 30 minutes to fully dissolve. Then add 1 mL of ammonia water and 1 mL of VTES (triethoxyvinylsilane), stir evenly, and then add 0.42 mL of 37%-40% formaldehyde solution. The above mixed solution reacts at room temperature for 2-24 hours and becomes a white suspension. The suspension is centrifuged, washed, and dried to obtain SiO2 with a size of 100-800 nm. 1.5 / C microsphere precursor;

[0081] (2) SiO 1.5 The precursor of the C / C microspheres and the core silicon with a D50 of 10 μm were mixed in a mass ratio of 4:96, and the mixture was ball-milled at 300 rpm for 30 min and then taken out to obtain SiO 1.5 / C microsphere precursor coated silicon material;

[0082] (3) The material obtained in step (2) was introduced into a tubular furnace under Ar atmosphere protection, heated to 900°C at a rate of 5-10°C / min, and kept at this temperature for 5 hours to obtain SiO 1.5SiO anode material coated with / C microspheres 1.5 / C@Si, where the mass of the coating layer accounts for 4% of the total mass of the anode material. In the embodiments of the present invention, resorcinol and formaldehyde are condensed to form a C-H-O network, and after high-temperature curing, the final carbon structure is formed.

[0083] Example 2

[0084] A preparation method of an SiO anode material coated with Al2O3 / C microspheres includes:

[0085] (1) Dissolve Al(NO3)3·9H2O and citric acid in water in a certain proportion, and adjust the pH of the solution to about 2 with concentrated hydrochloric acid to obtain a transparent solution. Weigh a certain mass of the core material SiO with D50 = 5μm, disperse it in the above transparent solution, then add pyrrole solution thereto, stir for 30 min to make it fully dispersed, and then add a certain proportion of FeCl3 thereto and continue to react for 6 - 24 h. Separate the reactants by centrifugation or filtration, and wash and dry them with deionized water and ethanol multiple times to obtain an SiO material coated with Al2O3 / C microsphere precursors;

[0086] (2) Introduce the material obtained in step (1) into a tubular furnace and heat it to 900°C at a heating rate of 5 - 10°C / min under Ar atmosphere protection. After holding for 5 h, collect the Al2O3 / C microsphere precursor-coated SiO material Al2O3 / C@SiO, where the mass of the coating layer accounts for 8% of the total mass of the anode material. Figure 5 The scanning electron microscope image of the Al2O3 / C@SiO anode material prepared in this example is shown. The figure shows that the Al2O3 / C@SiO anode material has an obvious core-shell structure. The Al2O3 / C microspheres are uniformly stacked on the surface of the inner core to form a coating layer. The coating layer can protect the inner core SiO from direct contact with the electrolyte and prevent side reactions such as electrolyte decomposition, and relieve the expansion of SiO. At the same time, the carbon structure in the coating layer can ensure the electronic conductivity of the material.

[0087] Example 3

[0088] A kind of SiO x (1.2 < x ≤ 2.0) / C microsphere-coated Si anode material preparation method, including:

[0089] (1) Measure 60 mL of deionized water and 2 mL of ammonia water and mix them evenly. Dropwise add 2 mL of VTMS (trimethoxyvinylsilane) thereto, and keep stirring at a water bath temperature of 80°C. After reacting for 6 h, obtain a SiOx / C microsphere precursor with a uniform particle size of D50 of 300 nm. As Figure 6, which is a scanning electron microscope image of the SiOx / C microsphere precursor of this embodiment, shows that the SiOx / C microsphere precursor with uniform particle size is obtained in this embodiment, which is spherical or quasi-spherical particles.

[0090] (2) SiOx / C microsphere precursor and core silicon with D50 = 10 μm were mixed at a mass ratio of 5:95, ball milled at 300 rpm for 30 min, and then taken out to obtain SiO x / C microsphere precursor coated silicon material;

[0091] (3) The material obtained in step (2) was introduced into a tubular furnace under Ar atmosphere protection, heated to 1050°C at a rate of 5-10°C / min, and kept at this temperature for 5 hours to obtain SiO 1.5 SiO / C microsphere-coated Si anode material x / C@Si, wherein the mass of the coating layer accounts for 5% of the total mass of the negative electrode material. Since no additional carbon source is added in this embodiment, SiO x / C microspheres have a low carbon content. In order to maintain the conductivity of the microspheres, the curing temperature is set to 1050℃ to increase the graphitization degree of carbon.

[0092] In order to strongly support the beneficial effects brought about by the technical solutions in Examples 1-3, the conductivity and battery cycle performance of the negative electrode materials of Examples 1-3 were tested respectively, and the corresponding uncoated negative electrode materials were used as controls.

[0093] The specific operation of the battery cycle performance test is: the negative electrode materials prepared in the three embodiments are mixed with commercial artificial graphite to form a 600mAh / g negative electrode material to prepare soft-pack batteries, and the cycle performance is compared under the same battery model (386174), the same capacity (~3.7Ah), the same current density (1.1+0.7C step charge) and the test temperature (25°C). The results are as follows Figure 7 And as shown in Table 1.

[0094] Table 1 Conductivity and battery cycle performance results of different negative electrode materials

[0095]

[0096] Through Table 1 and Figure 7 It can be found from the results that the silicon-based negative electrode material with a coating layer in the embodiment of the present invention has a significantly improved conductivity and a significantly improved long cycle capacity of the battery compared to the silicon-based negative electrode material before coating.

Claims

1. A negative electrode material, characterized in that: It includes an inner core and a coating layer coated on the surface of the inner core, wherein the coating layer includes a first carbon material and oxides / carbon microspheres dispersed in the first carbon material, wherein the oxides / carbon microspheres are secondary particles formed by a composite of nano oxide particles and a second carbon material, wherein the nano oxide particles include one or more of metal oxide particles and silicon oxide particles, wherein the first carbon material and the second carbon material form a conductive carbon network, and the particle size of the inner core is 500nm to 50μm.

2. The negative electrode material according to claim 1, characterized in that The particle size of the nano-oxide particles is less than or equal to 10 nm.

3. The negative electrode material according to claim 1, characterized in that The particle size of the oxide / carbon microspheres is 50 nm-1 μm.

4. The negative electrode material according to claim 1, characterized in that Inside the oxide / carbon microspheres, the nano oxide particles and the second carbon material are evenly distributed.

5. The negative electrode material according to claim 1, characterized in that Part or all of the first carbon material and the second carbon material are homogeneous carbon.

6. The negative electrode material according to claim 1, characterized in that The metal oxide particles include one or more metal oxide particles formed by one or more metal elements of Mg, Al, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn and Li and oxygen.

7. The negative electrode material according to claim 1, characterized in that The mass of the coating layer accounts for 1%-20% of the total mass of the negative electrode material.

8. The negative electrode material according to claim 1, characterized in that In the coating layer, the mass content of the nano oxide particles is 20%-90%.

9. The negative electrode material according to claim 1, characterized in that The coating layer has a thickness of 100 nm-5 μm.

10. The negative electrode material according to claim 1, characterized in that The silicon oxide particles have a silicon-oxygen atomic ratio of 1:1.2-2.

11. The negative electrode material according to claim 1, characterized in that The specific surface area of ​​the negative electrode material is 1-20 m 2 / g.

12. The negative electrode material according to claim 1, characterized in that The core is made of silicon-based material, and the silicon-based material includes one or more of elemental silicon, silicon oxide, silicon carbon, and silicon alloy.

13. The negative electrode material according to claim 1, characterized in that The inner core is a tin-based material, and the tin-based material includes one or more of elemental tin and tin oxide.

14. The negative electrode material according to claim 1, characterized in that The core is one or more of silicon, silicon oxygen, silicon carbon, silicon oxygen carbon, tin, tin oxide, and phosphorus.

15. The negative electrode material according to claim 1, characterized in that The negative electrode material further includes a protective layer disposed on the surface of the coating layer, and the material of the protective layer includes a carbon material and / or a conductive polymer.

16. A method for preparing a negative electrode material, characterized in that: include: Mixing an oxide precursor, a carbon source precursor, and a core material together, so that the oxide precursor and the carbon source precursor form an oxide / carbon microsphere precursor in situ on the surface of the core material, and obtaining a core material with the oxide / carbon microsphere precursor coated on the surface; or Firstly, the oxide precursor and the carbon source precursor are mixed to prepare an oxide / carbon microsphere precursor, and then the oxide / carbon microsphere precursor is coated on the core material to obtain a core material with the oxide / carbon microsphere precursor coated on the surface; The core material whose surface is coated with an oxide / carbon microsphere precursor is subjected to a high-temperature carbonization treatment at 800°C-1100°C to obtain a negative electrode material, wherein the negative electrode material comprises a core and a coating layer coated on the surface of the core, wherein the core is a silicon-based material or a tin-based material, wherein the coating layer comprises a first carbon material and oxide / carbon microspheres dispersed in the first carbon material, wherein the oxide / carbon microspheres are secondary particles composited with nano-oxide particles and a second carbon material, wherein the nano-oxide particles comprise one or more of metal oxide particles and silicon oxide particles, and wherein the first carbon material and the second carbon material are continuously distributed to form a conductive carbon network.

17. The preparation method according to claim 16, characterized in that: During the high temperature carbonization treatment, the temperature is raised to 800°C-1100°C at a heating rate of 2-10°C / min.

18. The preparation method according to claim 16, characterized in that: The high temperature carbonization process is carried out under vacuum or protective atmosphere.

19. The preparation method according to claim 16, characterized in that: The core material with the oxide / carbon microsphere precursor coated on the surface is prepared by one or more methods including sol-gel method, hydrothermal method and co-precipitation method.

20. The preparation method according to claim 16, characterized in that: The oxide precursor includes one or more of silane containing Si-O bonds, metal oxygen acid salts, metal alcohol compounds, and metal ester compounds.

21. The preparation method according to claim 16, characterized in that: The carbon source precursor includes one or more of phenols, aldehydes, thiophene, pyridine, pyrrole, aniline, and imidazole.

22. A battery, characterized in that: It comprises a positive electrode sheet, a negative electrode sheet, a separator, and an electrolyte, wherein the negative electrode sheet comprises a negative electrode active material, and the negative electrode active material comprises the negative electrode material as described in any one of claims 1 to 15.

23. A terminal, characterized in that: It comprises a terminal shell, and a circuit board and a battery located inside the terminal shell, wherein the battery is electrically connected to the circuit board for supplying power to the circuit board, and the battery comprises the battery according to claim 22.

Citation Information

Patent Citations

  • Negative active material and lithium battery including the material, and method for manufacturing the material

    CN104701505A